2021
DOI: 10.1155/2021/5539851
|View full text |Cite
|
Sign up to set email alerts
|

The Weight of HLA-DPA1 rs3077 Single Nucleotide Polymorphism in Prostate Cancer, a Multicenter Study

Abstract: Prostate cancer (PCa) has almost the highest genetic transmission that mimics an autosomal dominance hereditary pattern of cancers in some families. Its incidence in Arab countries was reported to be steadily increasing. Aim. To determine the relevance of HLA-DPA1 rs3077 (A/G) SNP with prostate cancer’s risk and/or severity. Subjects and Methods. Forty PCa patients and forty age matched patients with benign prostatic hyperplasia (BPH), as a control group, were enrolled in the study. Serum levels of urea, creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…DNA purity and concentration were assessed using a NanoDrop spectrometer. Genotyping of HLA‐DPA1rs3077(A/G) and HLA‐DQ‐rs3920 ( A/G ) was done using real‐time PCR (Applied Biosystems‐Life Technologies, California, USA), as described by Alenzi et al (2021). In each run, three water samples were used as blank controls and five randomly selected samples were repeated (to test the consistency).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA purity and concentration were assessed using a NanoDrop spectrometer. Genotyping of HLA‐DPA1rs3077(A/G) and HLA‐DQ‐rs3920 ( A/G ) was done using real‐time PCR (Applied Biosystems‐Life Technologies, California, USA), as described by Alenzi et al (2021). In each run, three water samples were used as blank controls and five randomly selected samples were repeated (to test the consistency).…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have reported a relation between HLA SNPs and different diseases such as gastric cancer (Huang et al, 2012; Lee et al, 2009; Li et al, 2005), breast cancer (Ghazy et al, 2014), ovarian cancer (Ghazy & El‐Etreby, 2016), prostate cancer (Alenzi et al, 2021) and viral infections (as HBV, HCV) (Ghazy et al, 2016, 2020). Such studies were conducted to evaluate either susceptibility, molecular pathogenesis, prognosis or response to treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For any viral infection, viral antigen presentation and induction of cellular immunity occurs mainly through human leukocyte antigen (HLA). Recently, we have studied the role of HLA-DP/DQ polymorphisms in many diseases as ovarian cancer (7), hepatitis C virus (HCV) infection and response to treatment (8), Prostate cancer (PCa) (9), Helicobacter pylori recurrence (10), and type 1 diabetes mellitus (T1DM) (11). Results of these studies showed variable results; for example, HLA-DPrs3077G allele was more frequent among PCa patients than the control group (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have studied the role of HLA-DP/DQ polymorphisms in many diseases as ovarian cancer (7), hepatitis C virus (HCV) infection and response to treatment (8), Prostate cancer (PCa) (9), Helicobacter pylori recurrence (10), and type 1 diabetes mellitus (T1DM) (11). Results of these studies showed variable results; for example, HLA-DPrs3077G allele was more frequent among PCa patients than the control group (9). However, HLA-DPrs3077A allele was associated with higher risk to ovarian cancer (7), HCV (8), H. pylori infection (10), and T1DM (11).…”
Section: Introductionmentioning
confidence: 99%